2016
DOI: 10.1038/leu.2016.187
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination of histone H3 drives IL-6 production by bone marrow mesenchymal stem cells in MGUS and multiple myeloma

Abstract: Multiple myeloma (MM), an incurable plasma cell malignancy, requires localisation within the bone marrow. This microenvironment facilitates crucial interactions between the cancer cells and stromal cell types that permit the tumour to survive and proliferate. There is increasing evidence that the bone marrow mesenchymal stem cell (BMMSC) is stably altered in patients with MM—a phenotype also postulated to exist in patients with monoclonal gammopathy of undetermined significance (MGUS) a benign condition that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 47 publications
1
45
0
1
Order By: Relevance
“…1F). In good accord with the previously published data [29], our clinical data showed that the HOXC10 mRNA levels were upregulated in MM-MSCs relative to those from ND (Fig. 1G).…”
Section: Stem Cellssupporting
confidence: 92%
“…1F). In good accord with the previously published data [29], our clinical data showed that the HOXC10 mRNA levels were upregulated in MM-MSCs relative to those from ND (Fig. 1G).…”
Section: Stem Cellssupporting
confidence: 92%
“…PAD2 and PAD4 may be important within B lineage cells for regulating IgG production or other pathways, although expression data for the PADs in B cells is conflicted [9, 14, 15, 52], or important in cells that regulate B cells. For example, PAD2 is upregulated in the bone marrow mesenchymal stem cells of patients with multiple myeloma, a plasma cell malignancy, driving production of IL-6, a molecule that supports plasma cells [53][54]. Perhaps in the absence of PAD2, IL-6 is reduced in the bone marrow microenvironment leading to reduced plasma cells and IgG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PADI2 is also found to be highly expressed in bone marrow mesenchymal stem cells (BMMSCs) [93]. These BMMSCs are key components for both the normal and transformed bone marrow niche.…”
Section: The Role Of Padi2 In Cancermentioning
confidence: 99%